2013
DOI: 10.1016/j.jhin.2012.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of surveillance for surgical site infections in Thika Hospital, Kenya

Abstract: SummaryBackgroundIn low-income countries, surgical site infections (SSIs) are a very frequent form of hospital-acquired infection. Surveillance is an important method for controlling SSI but it is unclear how this can best be performed in low-income settings.AimTo examine the epidemiological characteristics of various components of an SSI surveillance programme in a single Kenyan hospital.MethodsThe study assessed the inter-observer consistency of the surgical wound class (SWC) and American Society of Anesthes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
52
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(55 citation statements)
references
References 15 publications
(10 reference statements)
2
52
0
1
Order By: Relevance
“…It is worth noting that > 80% of Staphylococci isolates in the present study were methicillin-resistant and > 50% of Gramnegative pathogens were resistant to the commonly prescribed antibiotics such as cephalosporins, quinolones and trimethoprim/sulfamethoxazole. These findings, similar to previous reports from developing countries, 20,21,28 This study has some limitations. The first limitation is the absence of individual patient follow-up after discharge.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…It is worth noting that > 80% of Staphylococci isolates in the present study were methicillin-resistant and > 50% of Gramnegative pathogens were resistant to the commonly prescribed antibiotics such as cephalosporins, quinolones and trimethoprim/sulfamethoxazole. These findings, similar to previous reports from developing countries, 20,21,28 This study has some limitations. The first limitation is the absence of individual patient follow-up after discharge.…”
Section: Discussionsupporting
confidence: 91%
“…20,21 These measures include: maintaining perioperative blood glucose levels of less than 200 mg/dL; avoiding hair removal except when hair could interfere with an operation or, when hair removal is necessary, removing it with clippers; using appropriate antibiotics for antimicrobial prophylaxis ; conducting antimicrobial prophylaxis for the appropriate time (and discontinuing the prophylaxis within 24 h after the procedure); and requiring a chlorhexidine bath before the operation. 22 20,21,23,24 Perioperative antimicrobial prophylaxis is a well-established strategy for reducing the risk of SSI. However, in the present study, there were no significant differences in the rate of SSI between patients who received antibiotic prophylaxis and those who didn't.…”
Section: Discussionmentioning
confidence: 99%
“…The average number of beds in the surveyed hospitals was as follows: national hospitals; 372 (150-497), private hospitals; 206 (50-750), other hospitals 328 (156-500). The average number of clinical departments was as follows: national hospitals (excluding the two specialized hospitals); 18.0 (14-22), private hospitals 9.7 (6)(7)(8)(9)(10)(11)(12)(13)(14)(15); other hospitals 17.5 (15)(16)(17)(18)(19)(20). TUTH, which is one of the national hospitals, had 468 beds and 22 clinical departments.…”
Section: General Information On Hospitalsmentioning
confidence: 99%
“…In developing countries, where the incidence of infectious diseases is high and environmental conditions of healthcare facilities are poor, nosocomial infections may frequently occur, and some studies have reported a high incidence at healthcare facilities in these countries [4][5][6]. Effective nosocomial infection control is crucial in the healthcare facilities of developing countries, but in actual fact, attention to it is still limited and control measures are not functioning well in many facilities.…”
Section: Introductionmentioning
confidence: 99%
“…However, thousands of infections are recorded nationally every year post surgery, making surgical site infections commonly occurring in healthcare, ranging from superficial skin infections to much more severe conditions some in fact life-threatening [1]. A review studying surgical site infections in low-income countries and Africa in particular found that the frequency of surgical site infections were shockingly high in comparison to high-income countries [2].…”
Section: Introductionmentioning
confidence: 99%